(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the lexical and semantic features of some nicknames formed on the basis of English, French and German words in Oguz and Kipchak dialects of the Uzbek language in the Khorezm region of Uzbekistan.